1999
DOI: 10.1136/bjsm.33.6.401
|View full text |Cite
|
Sign up to set email alerts
|

Upright posture and maximal exercise increase platelet aggregability and prostacyclin production in healthy male subjects.

Abstract: Background-It is well accepted that heavy physical exertion can trigger the onset of myocardial infarction, but the mechanism is uncertain. As platelet and endothelial function play an important role in thrombotic events, platelet and prostacyclin responses to maximal treadmill exercise were studied. Methods/Results-The study subjects were 40 healthy men, mean (SEM) age 29 (5) years. Platelet aggregation was measured on a four channel aggregometer. Plasma 6-keto-prostaglandin F 1 was analysed using an enzyme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…The greater degree of hypovolemia induced by LBNP in this study also demonstrated coagulation activation by reducing PT and APTT. This is in line with the reported activation of coagulation during LBNP (38) and other orthostatic challenges (10,21,36). Because direct vascular damage due to arterial and venous catheter placement was likely minimal in our study, it is probable that other factors contributed to the coagulation response.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The greater degree of hypovolemia induced by LBNP in this study also demonstrated coagulation activation by reducing PT and APTT. This is in line with the reported activation of coagulation during LBNP (38) and other orthostatic challenges (10,21,36). Because direct vascular damage due to arterial and venous catheter placement was likely minimal in our study, it is probable that other factors contributed to the coagulation response.…”
Section: Discussionsupporting
confidence: 76%
“…However, it is unclear if markers of coagulation system activation respond similarly during these protocols. Reductions in central blood volume by LBNP (38) or orthostatic stress (10,21,36) activate the coagulation cascade; therefore, it is likely that central hypovolemia during BL elicits comparable changes in coagulation when the degree of central hypovolemia is similar between LBNP and BL.…”
Section: Our Study Provides Noteworthy Data That Directly Compare Blomentioning
confidence: 99%
“…Thus, lipid mediators may play an important role in adaptive responses to exercise that are evoked not only with classic injury or damaging stimuli. Heightened circulating COX-1-and COX-2-derived PGE 2 (28,50,66,70,107), PGF 2␣ (28,30), and 6-keto-PGF 1␣ (18,28,33,50,58,62,76,108) have been observed during continuous submaximal exercise. These transient changes appear to play an important role in the regulation of circulatory system responses during exercise, as NSAID administration can block exercise-induced muscle hyperemia and the cardiovascular pressor reflex (22,25,79).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, circulating PGs and LTs (with the exception of TXB 2 ) were unchanged immediately after resistance exercise, but exhibited a delayed peak elevation between ϳ1 and 2 h (PGD 2 , PGE 2 , PGF 2␣ , and LTB 4 ) and 24 h (6-keto-PGF 1␣ ) into recovery. That TXA 2 is the major product of platelet COX-1 and elevated TXB 2 immediately after exercise likely reflects an acute proaggregatory cardiovascular response, as has been observed during maximal, but not submaximal, aerobic exercise (33,50,58). PGs and LTs are classical proinflammatory lipid mediators, the physiological effects of which include vascular vasodilation, increased blood vessel permeability, and neutrophil chemotaxis/activation (57,75).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Once exposed to injuries, such as, high blood pressure or increased shear stress, their procoagulant activity prevails. 16,17 Although intensive exercise was shown to be associated with increased coagulability through a mechanism involving endothelial activation, 18 virtually no data are available regarding the effect of still standing on the coagulation cascade.…”
mentioning
confidence: 99%